Assessing the effect of Alpinia galanga extract on the treatment of SSRI-induced erectile dysfunction: A randomized triple-blind clinical trial - Akbarzadeh, Farzad; Eslamzadeh, Mahboubeh; Behravan, Ghazal; Ebrahimi, Alireza; Emami, Seyed Ahmad; Gilan, Atefe; Hoseinian, Najme Sadat (Frontiers in Psychiatry, 2023)
Objective SSRIs are considered the first line in the medical treatment of depression and anxiety disorders. One of their most common side effects, sexual dysfunction, has led many patients to discontinuing their medication and treatment course. Alpinia galanga, a plant from the ginger family, has been shown to enhance androgenic activity and sexual function. This study aimed to assess whether the addition of Alpinia galanga extract to the treatment regimen of adult males consuming SSRIs can improve SSRI-induced erectile dysfunction. Materials and Methods This triple-blind randomized clinical trial was conducted on 60 adult males who were being treated with SSRIs at the time of the study. The participants were divided into two groups, a group of 30 people receiving 500 milligrams of Alpinia galanga extract, and a group of 30 subjects receiving placebo. The population were re-assessed on week 2 and week 4 of the study using the international index of erectile function (IIEF), the Beck Depression Inventory, and the Beck Anxiety Inventory. In all the tests, a p-value of 0.05 was considered as the cut-off for significance. Results At the beginning of the study, the IIEF score of the placebo group and the intervention group were 10.6±3.8 and 11.2±4.8, respectively, which were not significantly different (p-value=0.577). By week 4 of the study, the IIEF scores of the control group and the Alpinia galanga group had increased to 13.7±4.3 and 17.4±3.7 respectively, which demonstrates a remarkably larger increase in the group receiving Alpinia galanga extract in comparison to the placebo group (p-value<0.001). Conclusion In this study, the effect of the addition of Alpinia galanga extract to the treatment regimen of male patients using SSRIs on the sexual dysfunction experienced by this group has been promising. Similar results, if proven, can aid both patients and clinicians in making and following better treatment plans with more pleasant outcomes.